Annotated list of the assassin bugs (Heteroptera: Reduviidae) of Belize, with the description of two new species - Swanson, Daniel R.; Chordas, Stephen W. Iii (Zootaxa, 2018)
Fifty-one species of Reduviidae (Hemiptera: Heteroptera) are recorded from Belize; literature citations are provided where relevant, and specimen data are included for examined material. Thirteen previously-described species are reported from Belize for the first time, ten of which represent new generic records: Eupheno histrionicus Stål, 1862 (Cetherinae); Ghinallelia signoreti (Dohrn, 1860) (Emesinae); Rasahus albomaculatus (Mayr, 1865) (Peiratinae); Leogorrus interruptus Champion, 1899; Microlestria laevis Champion, 1899; Nalata quadrituberculata Champion, 1899; Nalata setulosa Stål, 1862; Pseudozelurus superbus (Champion, 1899); Zelurus spinidorsis (Gray, 1832) (all Reduviinae); Oncerotrachelus conformis Uhler, 1894; Saica fuscipes Stål, 1862 (both Saicinae); Gnathobleda litigiosa Stål, 1862; and Stenopoda wygodzinskyi Giacchi, 1969 (both Stenopodainae). Among the ten subfamilies reported, Belizean records for one subfamily, Saicinae, are reported for the first time. Accompanying the checklist are the descriptions of Castolus omega Swanson sp. nov. (Harpactorinae) and Pygolampis aptena Swanson sp. nov. (Stenopodainae).